Раскопки поселения поздней бронзы у с. Давыдо-Никольское в 2007—2008 гг. - Пробейголова, А.С. (Археологічні дослідження в Україні, 2009)
The article contains the results of the excavations at Davydo-Mykilske multilayer settlement near the Siverskyi Donets River in 2007—2008. During the works two horizons of Bilozerska and Zrubna cultures have been determined. The remains of Zrubna culture dwellings were discovered.